Stock Market Behaviour in Response to Political Events: A Case of Pakistan Major Political Events - Samdani, Saima; Ullah, Hamid; Nabi, Ghulam; Zeb, Naveeda; Khan, Muhammad Kamran; Ahmed, Masood; khan, Azhar (The journal of contemporary issues in business and government, 2021)
Purpose of this research is to unearth the effect of significant political events on stock market performance and volatility of Pakistan during the period 2013 to 2018.Event study methodology is employed to investigate the stock market behaviour in response to major political events i.e. the China Pakistan Economic Corridor CPEC (MOU), Prime Minister Nawaz Sharif disqualification, and the Elections held on 25th July 2018,in terms of four indexes (i.e. KSE 100 index, KSE all share indexes, KSE-30 index and KMI 30 index).Findings demonstrated that political events influence the stock market according to their nature.The contribution of this study is two folds. The effect of political events on stock market performance is relatively understudied in the context of Pakistan.Contrary to previous studies; the current study examined the effects on all the indexes quoted by Pakistan Stock Exchange(PSX).